2018
DOI: 10.1097/tp.0000000000001929
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes of Kidney Transplantation in Infants (Age < 2 years)

Abstract: Infants deserve earlier consideration for KTx. Length of initial hospital stay and patient and graft survival rates after KTx have improved in infants since 1984.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 38 publications
5
24
3
Order By: Relevance
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies .…”
Section: Discussionsupporting
confidence: 86%
“…The use of our protocol has resulted in both patient and graft survival that compare favorably with recently published studies . In particular, DGF occurred in two (3.2%) patients in our study population, as compared to 6%‐10% reported in prior studies . Due to multiple factors, ranging from cold ischemia time, hypotension, and donor age, DGF is a significant risk factor for the development of both acute rejection and subsequent graft loss .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Unlike adult renal transplantation, the etiologies of pediatric ESRD are more commonly due to CAKUT, lower urinary tract dysfunction (neurogenic bladder, reflux, or posterior urethral valves), hereditary nephropathies, and glomerulonephritis . Patient survival rates within the first year of transplant have improved in recent years due to advancements in immunosuppression, surgical technique, organ allocation policies, and rates of living donor transplantation . Consequently, recent studies have also shown that compared to long‐term dialysis, early renal transplantation for children with ESRD may offer good mental and physical quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…Early transplant is recommended to avoid cardiovascular morbidity and infection risk associated with long-term dialysis [51-53]. Size at the time of transplant varies with some centers transplanting infants as small as 5 kg, but most providers aim for transplant once the child is > 10 kg.…”
Section: Approach To Fetal and Neonatal Therapy For Epramentioning
confidence: 99%